Fate, dissemination of Bacillus subtilis spores in gastrointestinal tract of broiler chicken and its effect on intestinal flora and digestive enzyme activities - TANG Jiang-wu; SUN Hong; YAO Xiao-hong; WU Yi-fei; WANG Xin (浙江大学学报. 农业与生命科学版)
Two hundred forty one-day-old AA broilers were randomly divided into 2 groups with 6 replicates, administrating the same antibiotics-free basal diet. After 3 d feeding, broilers of control group and experimental group were respectively dosed with 0.5 mL sterile water or spore (1.5×108 CFU·mL-1), aiming to examine the internal fate and dissemination of Bacillus subtilis spores in the intestine of AA broiler as well as its effects on changes of intestinal flora and activity of digestive enzymes. Spores were counted and enzyme activities were measured at different sampling time, while the intestinal flora was determined by using polymerase chain reaction-denaturing gradient gel electrophoresis (PCR-DGGE) method. The results showed that: feeding spores began to germinate in the duodenum; vegetative cells outnumbered spores in the jejunum whereas most of B. subtilis spores were detected in ceca. Spores in faeces reached its peak value of 7.9×104 CFU·g-1 at 24 h after dosed, then were gradually decreased. After 72 h, no spores could be detected. PCR-DGGE combined with principal component analysis (PCA) showed significant changes in the intestinal flora during passage of B. subtilis spores, while Lactobacillus sp. population in experimental group increased, compared with the control group. Amylase, trypsin and total protease activities in duodenum, lipase activity in jejunum and total protease activities in cecum were significantly higher than control group (P<0.05) after 12 h of spores dosing. The results above confirm that spores can survive the gastric barrier well, germinate in the intestine of AA broiler, and are detected up to 72 h. In such process, intestinal digestive enzyme activity and microflora are improved.